Instant Oracle Database and PowerShell how-to : utilize the power of Microsoft's powerful scripting engine to automate database tasks with Oracle from PowerShell /: utilize the power of Microsoft's powerful scripting engine to automate database tasks with Oracle from PowerShell. (2013) - Unknown
No abstract available